2022
DOI: 10.3389/fpubh.2022.940956
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccine Efficacy Against the SARS-CoV-2 Omicron: A Systemic Review and Meta-Analysis

Abstract: BackgroundCOVID-19 is a respiratory illness caused by SARS-CoV-2. The most recent variant is Omicron (line B.1.1.529), which was first identified in South Africa in November 2021. The concern with this variant is the ineffectiveness of vaccines currently available. We aim to systematically evaluate the effectiveness of the currently available COVID-19 vaccines and boosters for the Omicron variant.MethodsWe searched the PubMed, Embase, the Cochrane Library and Web of Science databases from inception to June 5th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Studies showed that vaccine effectiveness after receipt of both 2 and 3 doses was lower during the Omicron-predominant period than during the Delta-predominant period, and that the effectiveness of the booster dose is decreasing over time [20] , [21] . In accordance with this, our study did not find a significant difference between having a booster dose or not in the rate of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that vaccine effectiveness after receipt of both 2 and 3 doses was lower during the Omicron-predominant period than during the Delta-predominant period, and that the effectiveness of the booster dose is decreasing over time [20] , [21] . In accordance with this, our study did not find a significant difference between having a booster dose or not in the rate of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The study period coincided with the third pandemic wave in Croatia and the rise of the SARS-CoV-2 B.1.1.7 (Alpha) variant for which attenuated vaccine efficacy was observed, a continuing trend for variants of concern that followed [ 43 , 44 , 45 ]. Compared to healthy controls, hematologic patients showed an even faster decline in neutralizing antibody titers for B.1.351 (Beta) and B.167.2 (Delta) variants [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional humoral response after vaccination was lower against variants of concern (VOC) (i.e., Alpha, Beta, and Delta) vs wildtype [ 8 ]. More recently, the VOC Omicron has also raised concerns [ 9 ]. Even after booster dose administration, vaccination neutralization against the Omicron variant was lower than against other VOC [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the VOC Omicron has also raised concerns [ 9 ]. Even after booster dose administration, vaccination neutralization against the Omicron variant was lower than against other VOC [ 9 , 10 , 11 , 12 ]. In addition, numerous factors influence vaccine effectiveness.…”
Section: Introductionmentioning
confidence: 99%